DISKURSUS PEMIKIRAN HASSAN HANAFI: STUDI ATAS METODE PENAFSIRAN FENOMENOLOGI DAN EMANSIPATORIS - Sopiyan Iqbal; Muh. Azhar Kholidi (Penerbit Hellow Pustaka, 2025)
This paper discusses one of the renowned Muslim thinkers, Hassan Hanafi. This study will focus on the phenomenological and emancipatory interpretation methods proposed by Hassan Hanafi. This paper is analyzed descriptively using library sources, both through Hassan Hanafi's works and other related works. In general, it can be concluded that Hanafi formulated a methodology for interpreting the Qur'an not based on the established 'ulûm al-Qur'ân theories that have been widely used by Islamic scholars in interpreting the Qur'an, but rather through a philosophical approach, thus giving rise to a liberation hermeneutics. As a figure with a general idea of liberation theology, Hassan Hanafi employs phenomenology to unravel and utilizes an emancipatory perspective to mobilize.